Working Environment and Workload towards the Job Satisfaction: A Study of Non-Academic Administrative Officers of State Higher Education Institutions in Sri Lanka - Pathiranage, T.D.D.; Khatibi, Ali; Azam, S.M. Ferdous; Tham, Jacquline (Journal of Ecohumanism, 2024)
In the present world, issues related to working environment, workload and job satisfaction are intense in most occupations and more severe among professionals. Notably, workforce in higher education institutions all over the world are undergoing these issues. In this study, the researcher tried to identify the impact of working environment and workload on job satisfaction. A sample of 300 non-academic administrative officers has drawn from 9 higher education institutions in Sri Lanka. A structured questionnaire has been administered among the respondents by applying quantitative approach. Analysis of Variance (ANOVA), Analysis of Regression, and Correlation Analysis have been used to achieve the study objectives. The results discovered that the working environment has a significant impact on job satisfaction of non-academic administrative officers of higher education institutions in Sri Lanka. Further, the study highlighted that workload does not significantly affect job satisfaction of non-academic administrative officers of higher education institutions in Sri Lanka. Nonetheless, the study highlights the importance of dealing with job satisfaction of non-academic administrative officers of higher education sector related to workload and unfavorable working environment for the well-being of the Institute and individual employee.